John Dewey and Confucian thought - Behuniak, James (State University of New York Press, 2019)
"In this expansive and highly original two-volume work, Jim Behuniak reformulates John Dewey's late-period "Cultural turn" and proposes that its next logical step is an "intra-Cultural philosophy" that goes beyond what is commonly known as "comparative philosophy." Each volume models itself on this new approach and argues that early Chinese thought is poised to join forces with Dewey in meeting an urgent cultural need: namely, helping the Western tradition to correct its outdated Greek-medieval assumptions, especially where these result in pre-Darwinian inferences about the world. Relying on the latest findings in Chinese philosophy, these volumes establish "specific philosophical relationships" between Dewey's ideas and early Chinese thought for this purpose, showing how together they can assist us in getting our thinking "back in gear" with the world as it is currently known through the biological, physical, and cognitive sciences. Volume Two: Dao and Culture builds upon Volume One: Dao and Nature to argue that "Chinese natural philosophy" is the proper hermeneutical context in which to understand early Confucian thought. It engages Dewey with themes generally associated with "Confucianism," including education, tradition, ethics, the family, human nature, and religiousness. The volume assesses Dewey's visit to China (1919-1921) as a multi-faceted "intra-Cultural" episode: one that includes not only what Dewey taught his Chinese audiences, but also what he learned from China and what overseas Chinese students learned in the United States"-- Provided by publisher
Keywords: Dewey, John, -- 1859-1952 -- Knowledge -- Philosophy, Confucian.; Dewey, John, -- 1859-1952 -- Travel -- China.; Dewey, John, -- 1859-1952; Philosophy, Confucian.; Philosophy, Chinese.; Philosophy, Comparative.; East and West.; Philosophie confucéenne.; Philosophie chinoise.; Philosophie comparée.; East and West; Philosophy, Chinese; Philosophy, Comparative; Philosophy, Confucian; Travel; China